From Magma Formation to Eruption: Temperature Path of Two Late Carboniferous Post‐Collisional Calderas (Bohemian Massif) - I. Olšanská; F. Tomek; C. Robustelli Test; E. Zanella; M. Svojtka; J. Trubač; F. Cifelli; F. Finger (Geochemistry, Geophysics, Geosystems)
Abstract The thermal evolution of magmatic systems of the Altenberg‐Teplice and Tharandter Wald calderas, which erupted during the terminal post‐collisional phase of the Variscan orogeny in the Bohemian Massif, was investigated. The zircon saturation temperatures and Ti‐in‐zircon thermometer indicate that the intrusive and extrusive units of the two calderas were sourced from medium‐ to high‐temperature (∼770–930°C) felsic lower crustal magma. Using an integrated rock‐magnetic and paleomagnetic approach through thermal demagnetization and stepwise thermomagnetic curves, it was estimated that intracaldera ignimbrites reached temperatures of 550–600°C. The low‐temperature component (350–450°C) likely corresponds to the alteration of magnetic minerals during cooling or late‐stage magmatic/hydrothermal events. Placing these findings in the broader context of Variscan post‐collisional magmatism might suggest a trend of decreasing magma temperatures from 330 Ma to 302 Ma within the two lower‐to mid‐crustal (Moldanubian) and upper‐crustal (Saxothuringian) units of the Bohemian Massif, possibly reflecting the cooling of the hot collisional orogen. Lastly, we suggest that a combination of zircon temperature estimates with the rock‐magnetic methods may provide a comprehensive framework for further research on the thermal evolution of felsic magmatic systems.